LRH-1 agonism favours an immune-islet dialogue which protects against diabetes mellitus - Cobo-Vuilleumier, Nadia; Lorenzo, Petra I; García Rodríguez, Noelia; Herrera Gómez, Irene de Gracia; Fuente-Martin, Esther; López-Noriega, Livia; Mellado-Gil, José Manuel; Romero-Zerbo, Silvana Yanina; Baquié, Mathurin; Lachaud, Christian Claude; Stifter, Katja; Perdomo, German; et al. (Nature Research, 2018)
Type 1 diabetes mellitus (T1DM) is due to the selective destruction of islet beta cells by immune cells. Current therapies focused on repressing the immune attack or stimulating beta cell regeneration still have limited clinical efficacy. Therefore, it is timely to identify innovative targets to dampen the immune process, while promoting beta cell survival and function. Liver receptor homologue-1 (LRH-1) is a nuclear receptor that represses inflammation in digestive organs, and protects pancreatic islets against apoptosis. Here, we show that BL001, a small LRH-1 agonist, impedes hyperglycemia progression and the immune-dependent inflammation of pancreas in murine models of T1DM, and beta cell apoptosis in islets of type 2 diabetic patients, while increasing beta cell mass and insulin secretion. Thus, we suggest that LRH-1 agonism favors a dialogue between immune and islet cells, which could be druggable to protect against diabetes mellitus.
Keywords: Diabetes; Type 1 diabetes mellitus (T1DM); Liver receptor homologue-1 (LRH-1); LRH-1 agonist; Pharmacological therapy; Beta cells; Survival; Inflammation